PEMIMPIN YANG IDEAL DALAM MASYARAKAT MELAYU - juswandi, Juswandi (Jurnal Ilmu Budaya, 2012)
In Malay society, a leader is an important aspect. For that reason, religion is used as guideline to determine good leader, in this case Islamic doctrine. The society awares that a leader has important role, that's why the motto "adat bersandi syara, dan syara' bersendikan kitabullah" is used which means the tradition would be based on religion and holy Qur'an.